2000
DOI: 10.1039/b006201o
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of tetrasubstituted imidazoles catalyzed by zeolite HY and silica gel under microwave irradiation

Abstract: Four-component condensation of benzil, aromatic aldehydes, primary amines and ammonium acetate catalyzed by zeolite HY and silica gel without any solvent under microwave irradiation leads to tetrasubstituted imidazoles in high yields and purity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(94 citation statements)
references
References 15 publications
1
92
0
1
Order By: Relevance
“…17 The availability of microwave technology for synthetic purposes has allowed the efficient preparation of 2,4,5-trissubstituted and 1,2,4,5-tetrassubstituted imidazoles. Further observed benefits, that were occasionally associated with solid supports such as silica, alumina, clays, amongst others, [11][12][13] included improved yields, and dramatic reductions in reaction time and quantities of solvent used (AcOH). 14,15 Interestingly, the best supports found in these studies were always the acidic in nature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…17 The availability of microwave technology for synthetic purposes has allowed the efficient preparation of 2,4,5-trissubstituted and 1,2,4,5-tetrassubstituted imidazoles. Further observed benefits, that were occasionally associated with solid supports such as silica, alumina, clays, amongst others, [11][12][13] included improved yields, and dramatic reductions in reaction time and quantities of solvent used (AcOH). 14,15 Interestingly, the best supports found in these studies were always the acidic in nature.…”
Section: Resultsmentioning
confidence: 99%
“…The low yields for 3 and 4 are in accordance with literature data, where acidic conditions afforded better results. [11][12][13]17 In addition, it was also investigated whether these reactions could occur efficiently without a support or microwave energy (other conditions kept equal). The experiments were carried out for the synthesis of compound 2a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another efficient method is heating cyanoacetamide and methyl acetoacetate in a microwave oven [41]. Balalaie et al [42][43][44][45][46][47][48] have reported an efficient three component condensation of alkyl cyanoacetates, primary amines, and β-ketoesters with higher yields on the surface of silica gel, montmorillonite K-10, zeolite, and acidic alumina under microwave irradiation, the obtained products 19a-h in yields ranging from 91 to 93%. These compounds have two tautomeric forms, and in solution there is a very fast equilibration between them [49].…”
Section: Synthetic Approaches To Arylazopyridones and Arylazothienopymentioning
confidence: 99%